2012
DOI: 10.1002/cam4.20
|View full text |Cite
|
Sign up to set email alerts
|

GM‐CSF enhances tumor invasion by elevated MMP‐2, ‐9, and ‐26 expression

Abstract: Granulocyte–macrophage colony-stimulating factor (GM-CSF) promotes tumor progression in different tumor models in an autocrine and paracrine manner. However, at the same time GM-CSF is used in cancer therapies to ameliorate neutropenia. We have previously shown in GM-CSF and G-CSF expressing or negative skin or head and neck squamous cell carcinoma that GM-CSF expression is associated with a highly angiogenic and invasive tumor phenotype. To determine the functional contribution of GM-CSF to tumor invasion, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 48 publications
3
58
0
2
Order By: Relevance
“…Normally, TIMPs specifically combine with MMPs and keep their activity in a dynamic balance. However, once this balance is broken, invasion and metastasis of cancer cells is induced (6)(7)(8)(9). The imbalance between TIMPs and MMPs has been recognized as the main mechanism for promoting the invasive processes of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Normally, TIMPs specifically combine with MMPs and keep their activity in a dynamic balance. However, once this balance is broken, invasion and metastasis of cancer cells is induced (6)(7)(8)(9). The imbalance between TIMPs and MMPs has been recognized as the main mechanism for promoting the invasive processes of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3). Previous studies indicated that the expression of MMPs was regulated by their endogenous tissue inhibitors (TIMPs) (7)(8)(9). Thus, the expression levels of TIMP-1 and TIMP-2 in H1299 cells were examined by RT-qPCR and western blot analysis following treatment with 0, 5.0, 7.5 and 10.0 µM of allicin for 48 h. It was identified that allicin upregulated the RNA and protein levels of TIMP-1 and TIMP-2 in H1299 cells in a concentration-dependent manner (Fig.…”
Section: Allicin Alters Timp/mmp Balance In Lung Adenocarcinoma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the presence of macrophages, 5-FU treatment moderately to very strongly reduced the production of the majority of the pro-angiogenic (VEGF, eotaxin, thrombopoietin, bFGF) and pro-inflammatory (M-CSF, IL-1α, IL-1β, IL-12p40, MCP-1, G-CSF, GM-CSF, IL-6, FasL) proteins compared to their production in the untreated cell co-culture (Table I). The significant inhibition of these proteins could account for the high 5-FU cytotoxicity induced through the suppression of NF-κB since the aforementioned proteins have also been associated with the proliferation, survival and metastasis of cancer cells (7,8,10,31,32). Furthermore, NF-κB signaling has been described as the main mechanism for maintaining the pro-tumor phenotype of TAMs (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…12 The MMPs have been found in cases of inflammatory periodontal disease and are related to the progress of the periodontal disease. 3 Some authors have investigated the role of the MMPs 2 13,14 and 9 [13][14][15] in the progress of periodontitis, 16 but the participation of those enzymes in the process has not been totally established.…”
Section: Introductionmentioning
confidence: 99%